Writing as self-practice and rural school - Lara, Paola Andrea; Pulido-Cortés, Oscar (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The article presents the results of the research project "Escuela rural y escritura de sí: una experiencia pedagógica" (Rural school and writing of oneself: a pedagogical experience), in which writing is proposed as an experience of oneself and its interaction for the constitution of subjects in a Colombian rural school. The methodological perspective is based on the developments of the ethical moment in Michel Foucault who proposes himself as an exercise in thought involving the subjects' experience and their possibilities of transformation. The theoretical structure is divided into four categories: writing as self-practice, child-writer, work with rurality and reading as a spiritual exercise. The results and the discussion describe the writing exercises that were developed as a practical proposal in which the recipients interacted with the possibilities of writing, not only linguistic codes, but they also experienced writing as a way of constituting themselves. Finally, the article addresses some conclusions that highlight writing as an exercise that moves away from the instrumentalization and the decoding of language.